Quality of life of people with mental health problems: a synthesis of qualitative research - Connell Janice; Brazier John; O’Cathain Alicia; Lloyd-Jones Myfanwy; Paisley Suzy (Health and Quality of Life Outcomes, 2012)
Abstract Purpose To identify the domains of quality of life important to people with mental health problems. Method A systematic review of qualitative research undertaken with people with mental health problems using a framework synthesis. Results We identified six domains: well-being and ill-being; control, autonomy and choice; self-perception; belonging; activity; and hope and hopelessness. Firstly, symptoms or ‘ill-being’ were an intrinsic aspect of quality of life for people with severe mental health problems. Additionally, a good quality of life was characterised by the feeling of being in control (particularly of distressing symptoms), autonomy and choice; a positive self-image; a sense of belonging; engagement in meaningful and enjoyable activities; and feelings of hope and optimism. Conversely, a poor quality life, often experienced by those with severe mental health difficulties, was characterized by feelings of distress; lack of control, choice and autonomy; low self-esteem and confidence; a sense of not being part of society; diminished activity; and a sense of hopelessness and demoralization. Conclusions Generic measures fail to address the complexity of quality of life measurement and the broad range of domains important to people with mental health problems.